(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study was to determine whether the impact of repeat cesarean deliveries (CD) and abdominal adhesions on maternal and fetal complications exists in patients with a history of one previous CD and ones with three or more prior CD.Material and Methods: A total of one hundred-one pregnant women with a history of at least one previous CD were included in this prospective observational study. Participants were divided into two groups, patients with a single CD were added to the control group (n=56) and patients with a history of three or more CD were included in the study group (n=45). Preoperative scar characteristics and hemoglobin levels, intraoperative adhesion severity and grade were evaluated by using Linsky and Nair classifications for adhesion. In addition, duration of surgery, maternal complications and fetal status by using APGAR scoring system was analyzed, respectively.Results: Demographic features were comparable between the groups. The differences among the groups were found to be statistically significant in terms of adhesion intensity and grade (1.13 vs 0.42, p0.01 and 1.80 vs 0.89, p0.01, respectively), hemoglobin change (1.42 vs 0.83 mg/dL, p=0.011) and operation duration (47.60 vs 36.82 min, p0.01). In addition, APGAR scores were significantly lower in the multiple repeat cesarean group (1.min; 8.31 vs 8.64, p=0.02 and 5.min 9.37 vs 9.64, p=0.04, respectively).Conclusion: Multiple repeat CD was associated with poor obstetric outcomes and complications. Careful preoperative evaluation and preparation might be useful in reducing complications, especially in patients with a history of three or more CD.